The rotating cylinder electrode for studies of corrosion engineering and protection of metals—An illustrated review. (15th July 2017) - Walsh, F.C.; Kear, G.; Nahlé, A.H.; Wharton, J.A.; Arenas, L.F.
Graphical abstract: Highlights: Engineering science and practical features of the RCE are reviewed. Fluid flow around the RCE is normally turbulent; mass transport is predictable. Hybrid devices include bi-electrodes and combined micro/macro electrodes. RCE studies include inhibitors, flow-corrosion, coatings and surface films. Studies have diversified to nanofluids and cells having controlled current density. Abstract: The uniform flow generated at moderate rotation speeds, controlled mass transport rate and uniform current distribution make the RCE attractive for turbulent flow studies of corrosion and protection. Controlled flow and mass transport are characterised by peripheral velocity and mass transport coefficient. Important aspects in corrosion include metal dissolution, oxygen reduction, stability of surface oxide films and porosity of protective coatings. Computational studies allow fluid flow, current distribution and mass transport to be simulated; multiphase electrolytes and nanofluids have been experimentally studied over the last decade. Diverse uses of the RCE include cathodic protection, corrosion inhibitors and protective coatings.